Profiling of gene expression in bread wheat (Triticum aestivum L.) line PI 137739 in response to Russian wheat aphid (Diuraphis noxia Mordvilco) feeding - Oberholster, A.M. (University of Pretoria, 2013)
Thesis (PhD(Genetics))--University of Pretoria, 2005.